Development of Acid-Base Online Science Literacy Test Instruments - Anita Fadhilah; Sri Haryani (Pendidikan Kimia Unimus, 2021)
Facing the challenges of the 21st century, it is essential for students to have basic knowledge of science. The ability of scientific literacy relates to how students conceive the environment, health, economy, and problems of modern society which are more concerned to technology, advancement, and science development. Therefore, it is necessary to develop a scientific literacy test instrument that intends to measure students' scientific literacy skills. The objectives of this study were (1) to examine the feasibility of online scientific literacy test instrument in acid-base material, (2) analyze the level of validity and reliability of online scientific literacy test instrument in acid-based material, and (3) examine the profile of students' scientific literacy skills toward the test instrument. This Research and Development (R&D) 4D model which adapted by Thiagarajan (1974) shows the feasibility and validity of the scientific literacy test instrument with score 0.414 and 0.782, respectively. The profile of students' scientific literacy skills was in good criteria of 67%. The profiles of students' scientific literacy skills of competence aspects were 66%, 63%, and 72%, respectively.